“Análisis termográfico del alimentador n° 1 en media tensión de la subestación eléctrica San Rafael” - Farias Pullaguari, Andrés Leonardo (2021)
This research work focuses on performing the thermographic analysis on the medium voltage Feeder No. 1 belonging to provincial electrical company of Cotopaxi ELEPCO S.A, the purpose of the application of the thermography technique is to find the so-called hot spots within of the feeder, likewise generate solutions that benefit the electricity distribution company and consumer users. In the data collection, thermal imaging cameras are used in order to capture images of the elements and equipment inside the feeder that are likely to have some type of breakdown or failure, the considerations for proper measurement are used based on the peak hours of the electrical demand and the calibration of the cameras, the software Smarth View was used for the visual interpretation of the thermography. The results obtained that are presented in the thermography application, are interpreted in the actions according to their level of severity by the variable of the Temperature Delta found in the ANSI / NETA MTS-2011 standard and by the actions used by provincial electrical company of Cotopaxi ELEPCO S.A according to its tension level, the information obtained is directed towards the needs of the projection of a maintenance plan.